A new ground-dwelling Hemidactylus (Squamata: Gekkonidae) from Maharashtra, with a key to the Hemidactylus of India - Giri, Varad B.; Bauer, Aaron M. (Zootaxa, 2008)
A distinctive new species of ground-dwelling gecko of the genus Hemidactylus is described from the plateaus of the Western Ghats of Maharashtra, India. It is a member of a group of chiefly terrestrial Indian Hemidactylus species that have undivided, or only partly divided subdigital lamellae. The new species is most similar in appearance to the lowlandinhabiting Hemidactylus albofasciatus Grandison & Soman, 1963, but can be distinguished by its larger size and a suite of distinctive scalation and coloration characters. A key to the species of Hemidactylus currently known from the Republic of India is provided.